2022
DOI: 10.1016/j.pupt.2021.102108
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study regarding the predicted body weight-based dexamethasone therapy in patients with COVID-19 pneumonia

Abstract: Background The RECOVERY clinical trial reported that 6 mg of dexamethasone once daily for up to 10 days reduces the 28-day mortality in patients with coronavirus disease 2019 (COVID-19) receiving respiratory support. In our clinical setting, a fixed dose of dexamethasone has prompted the question of whether inflammatory modulation effects sufficiently reduce lung injury. Therefore, preliminary verification on the possibility of predicted body weight (PBW)-based dexamethasone therapy was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The study found an association between patients who did not receive corticosteroids and the increased expression of IL-6. Studies have shown the benefits of corticosteroids, such as dexamethasone, in reducing mortality in COVID-19 patients and reducing biomarkers such as ICAM-1 and ANGPT-2 [ 61 , 62 , 63 , 64 ]. Our results suggest that corticosteroids may benefit not only in reducing inflammation but also in inhibiting endothelial dysfunction and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The study found an association between patients who did not receive corticosteroids and the increased expression of IL-6. Studies have shown the benefits of corticosteroids, such as dexamethasone, in reducing mortality in COVID-19 patients and reducing biomarkers such as ICAM-1 and ANGPT-2 [ 61 , 62 , 63 , 64 ]. Our results suggest that corticosteroids may benefit not only in reducing inflammation but also in inhibiting endothelial dysfunction and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective cohort study involving patients with COVID-19 pneumonia who needed oxygen therapy and were treated with dexamethasone, remdesivir, and baricitinib, the PBW-based dexamethasone was not significantly better than the fixed-dose of dexamethasone for additional respiratory support, length of hospital stay, or oxygen demand. In our previous study, wherein PBW-based dexamethasone therapy shortened the length of hospital stay and duration of oxygen therapy and decreased the risk of using additional respiratory support without increasing serious adverse events or 30-day mortality, we found that an increased dose of dexamethasone based on PBW could be effective for some patients with COVID-19 [ 12 ]. However, PBW-based dexamethasone therapy appears to have no discernible effect in the current study, which included the use of powerful drugs like remdesivir and baricitinib.…”
Section: Discussionmentioning
confidence: 99%
“…First, administering baricitinib at an adequate time, immediately before hypoxemia occurs, may suppress hyperimmune response due to COVID-19. Sufficient, but not excessive, dexamethasone dosing, such as PBW-based dose dexamethasone, may be beneficial for patients whose inflammation progresses to hypoxemia, allowing the host inflammation to be properly controlled and preventing progression to the next stage of severe respiratory failure [ 12 ]. Glucocorticoids are known to be beneficial in stopping the inflammatory storm resulting from excessive activation of the immune response to viral infection if used at an adequate time during the disease course [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations